Mechanical Analysis of Lithium-Ion Batteries via Acoustic Impedance Spectroscopy - Soulen, Charles Edward; Sherrit, Stewart; Brandon, Erik; Liu, Ping (Meeting abstracts (Electrochemical Society), 2024)
Current state-of-charge (SOC) and state-of-health (SOH) estimation techniques for commercial Li-ion batteries (LIB) rely almost exclusively on voltage measurements and current integration, which produce large errors. Recently, acoustic techniques, primarily ultrasonic time-of-flight (US-ToF) have been used to reduce these errors, though cost, size, and voltage limitations prevent widespread use. Here, we introduce a practical alternative acoustic technique based on acoustic impedance spectroscopy (AIS). Using thin, cheap piezoelectric resonators, we can identify the acoustic resonances of commercial LIBs by measuring the complex electrical impedance of the resonator. In-operando AIS shows that these resonances are dependent on the bulk mechanical properties of the LIB, which change reversibly with SOC. Moreover, these mechanical changes induce unique responses in the resonance frequencies based on the modal structure of each resonance. Utilizing these changes, we can obtain a multi-dimensional trace of the SOC and SOH of a LIB. The application of AIS to LIBs represents a major step forward in practical acoustic characterization techniques.